2020
DOI: 10.3389/fnins.2019.01308
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Gravity: Gait Adaptations to Visual and Physical Inclines – A Virtual Reality Study

Abstract: Using advanced virtual reality technology, we demonstrate that exposure to virtual inclinations visually simulating inclined walking induces gait modulations in a manner consistent with expected gravitational forces (i.e., acting upon a free body), suggesting vision-based perception of gravity. The force of gravity critically impacts the regulation of our movements. However, how humans perceive and incorporate gravity into locomotion is not well understood. In this study, we introduce a novel paradigm for expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 41 publications
6
33
0
Order By: Relevance
“…We hypothesized that muscle activation patterns in response to vertical perturbations will differ from those in response to horizontal perturbations, because vertical perturbations generate unique challenges to equilibrium [6,13,21,27,28] (for a detailed rationale of a priori predictions and hypotheses, see Supplementary File #1). We further hypothesized that the role of vision would differ for vertical versus horizontal perturbations due to the critical role of vision in maintaining equilibrium [29][30][31], and because visual perturbations can signal gravitational changes as well as positional changes [32,33]. Specifically, since vertical visual scenes influence the apparent direction of gravity [33] and anteroposterior visual scenes act in advance of induced falls, we expect that visual conditions will modulate postural responses by adjusting the body against expected gravitational forces following vertical perturbations, and by activating muscles opposing a potential fall following horizontal perturbations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that muscle activation patterns in response to vertical perturbations will differ from those in response to horizontal perturbations, because vertical perturbations generate unique challenges to equilibrium [6,13,21,27,28] (for a detailed rationale of a priori predictions and hypotheses, see Supplementary File #1). We further hypothesized that the role of vision would differ for vertical versus horizontal perturbations due to the critical role of vision in maintaining equilibrium [29][30][31], and because visual perturbations can signal gravitational changes as well as positional changes [32,33]. Specifically, since vertical visual scenes influence the apparent direction of gravity [33] and anteroposterior visual scenes act in advance of induced falls, we expect that visual conditions will modulate postural responses by adjusting the body against expected gravitational forces following vertical perturbations, and by activating muscles opposing a potential fall following horizontal perturbations.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that magnitude of muscle activation, for instance, was progressive: smallest after visual perturbations, followed by (physical perturbations) dynamic-camera, static-camera, and finally, eyes-closed conditions that usually led to largest magnitudes. Visual sensory cues have been suggested to be suitable for balance-control regulation [59,60], and for locomotion modulation related to surface inclination changes [32]. Understanding the multisensory integration determining muscle activation patterns for postural control can have translational benefits for patients with sensory-integration dysfunctions, either to entrain compensations or to identify sources of sensory impairment.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…The evidence for motor actions is uncontroversial. Thus, it is well established that humans take gravity effects into account to control reaching movements optimally (Gaveau et al, 2011(Gaveau et al, , 2016, to guide locomotion on an inclined plane (Cano Porras et al, 2019), and to interact effectively with objects moving under Earth gravity (Zago et al, 2009;Lacquaniti et al, 2013). For instance, healthy participants easily intercept a target dropped vertically from above or rolling down an inclined plane, even with sparse visual information (e.g., Lee et al, 1983;Lacquaniti and Maioli, 1989a;Michaels et al, 2001;Zago et al, 2004;La Scaleia et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain stability during bipedal locomotion, the muscle system continuously adapts to changing walking conditions via a complex motor process that relays on multisensory integration (Wall-Scheffler CM, Chumanov E and B, 2011) that involves whole body adaptations (Kimel-Naor et al, 2017;Cano Porras et al, 2020). Particularly, walking on inclined surfaces lead to significantly different patterns and magnitudes of activation in lower limb muscles, as compared to leveled walking.…”
Section: Introductionmentioning
confidence: 99%
“…Inclined walking involves adjustment to gravitational forces. The exertion effect (uphill walking) and the braking effect (downhill walking) have been previously described and quantified (Cano Porras et al, 2020). Briefly, during uphill walking, the exertion effect counteracts the gravitational deceleration and allows the walker to maintain roughly stable gait speed pace, which is lower than natural speed during leveled walking (Sun et al, 1996;Sinitski et al, 2015;Kimel-Naor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%